APPLICATION DATA STORAGE ONLINE PROJECT AT PT. ANTARESINDO MANDIRI UTAMA WITH MYSQL - Linda Heliana; Linda Wahyu W. SKom,MMSI (Jurnal Sistem Informasi, 2008)
Data storage is very important in archiving files. Data storage is also a documentation companies in operation. In data storage is not only done at the operational office of the company. With the development employee of the company for mobility, data storage can be done online. Make it easy for employees to be able to store data anywhere, anytime. Will fully understand the performance of employees to be able to keep working as much as possible. So this is where the role of information technology is actually in use. With web media, not only capable of giving publicity to the company but also to facilitate employees in doing online data storage.